Hubungan Sikap Kerja dan Beban Kerja Dengan Keluhan Muskuloskeletal pada Nelayan - Fadillah Ulva; Gusrianti Gusrianti; Gusni Rahma (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Musculoskeletal complaints are complaints that occur in the skeletal muscles that are felt with complaints ranging from very mild complaints to very painful complaints. Musculoskeletal complaints can occur due to static and repetitive loading on the muscles that occurs for a long time. Musculoskeletal complaints can damage joints, ligaments and muscles. This can cause work stress due to the wrong working conditions. The purpose of this study was to determine the relationship between work attitude and workload with musculoskeletal complaints in fishermen. The type of research used is quantitative with a cross sectional stady design. This research was conducted in the Fisherman of Pasia Nan Tigo, Koto Tangah District. The number of samples is 30 people. This study uses primary data and secondary data. The measuring instrument used is a questionnaire. The data were analyzed univariately and bivariately using the Chi Square test. Based on the results of the study, it was known that there was a relationship between ape's attitude (p value: 0.23) and workload (p value: 0.009) with musculoskeletal complaints.